The secret garden - Burnett, Frances Hodgson, 1849-1924 ([Boston, Mass] : Thomson Heinle, 2007)
Ten-year-old Mary comes to live in a lonely house on the Yorkshire moors and discovers an invalid cousin and the mysteries of a locked garden
Title from container
Keywords: American literature; Orphans -- Fiction; Gardens -- Fiction; People with disabilities -- Fiction; Children with disabilities -- Fiction; Friendship in children -- Fiction; Yorkshire (England) -- Fiction